Inserção em programas de aprendizagem profissional : análise da formação das representações sociais de trabalho e de trabalho na adolescência a partir do relato das experiências de adolescentes aprendizes - Silva, Renata Danielle Moreira (2014)
The insertion of adolescents in the world of work is a controversial theme. Research in the fields of Humanities and Health Sciences suggest early labor insertion in adolescence may cause physical and psychosocial damage especially when work is done outside of prescribed legal standards. Adolescents in work condition, however, ascribe positive meanings to labor insertion, associating it to the development of financial autonomy, responsibility, construction of occupational identity and perspectives of future. The aim of this thesis was to identify and analyze the significance and meanings that adolescents inserted into professional apprenticeship programs (PAP) ascribe to work and to work insertion experience from the Theory of Social Representations. The study was developed in two stages (E1 and E2), using a theoretical, methodological and analytical triangulation. E1 was conducted under the structural approach of social representations (SR) and surveyed the evocations of 192 adolescents (90 girls and 102 boys) related to the inductor terms: adolescence, being adolescent and having to work and professional apprenticeship program, which were analyzed with the EVOC-2003 software. Evocated objects are part of a system of social representations that organize social practices related to labor insertion. E2, based on the processual approach of SR, was organized from the realization of semi-structured interviews with 27 adolescents (09 girls and 19 boys) aged 14 to 17 at two moments of PAP: at the beginning, when participants were in the program for four months, and at the end of the program, between 12 to 14 months since the first period of interviews. The scripts used in the two interview stages were similar and contained questions about PAP experiences, insertion process, adolescent routines, expectations about PAP, perceived changes and program evaluation. ALCESTE software and content analysis technique were used in interview analysis. In both stages of the study, hegemonic RS function as antinomical pairs, whose articulated meanings give rise to other anchor antinomies of emancipated SR of labor insertion: a) autonomy versus dependence on parents; b) job market experience versus inexperience; c) leisure/risk versus rushed and tiring routine; d) world of drugs and risk versus job market; e) theoretical PAP part versus practical part; f) apprentice adolescent versus generic adolescent. Thus, the adolescent which works in PAP perceives himself from the positivity that the working condition inculcates on adolescence. Work time experience in PAP added new meanings to initial SR and also changed the time perspective (TP): respondents give up important issues in the present (socializing with peers, leisure time, sleep time) in favor of a professional future. TP is a strategy of auto-regulation of the apprentices’ practices, increasing the persistency of behavior in present time, and is conducted by the SR related to labor insertion and to the continuity of professional life.